Lean Organization: from the Tools of the Toyota Production System to Lean Office - Chiarini, Andrea; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2013)
Lean Organization for Excellence describes the right way to implement lean thinking inside both manufacturing and service industries. After explaining the origins of the concept and discussing 'wastes' and value added, the book aims to set out a precise path of action. To this end, the so-called Hoshin Kanri method of defining business objectives and targets is explained, and a Value Stream Mapping tool that serves to identify all wastes is described. Subsequent chapters cover each of the TPS (Toyota Production System) tools, from 5S to SMED, and special attention is devoted to the Ducati case study, in which tools such as 5S and Kanban are applied. Lean metrics and the innovative Value Stream Accounting are discussed, and the closing chapter focuses on Lean Office for the service industry. Each chapter includes illustrations and tables relating to practical cases concerning the subject under consideration, based on real consultancy experiences.
Keywords: Economics; Economics/Management Science; Production/Logistics/Supply Chain Management